Optimization process of spin-coated black phosphorus/polydimethylsiloxane composite on microfiber as saturable absorber for ultrafast photonics - Ng, E.K.; Mohd Yusoff, N.; Lee, H.K.; Liew, J.Y.C.; Abu Bakar, M.H.; Zainol Abidin, N.H.; Alresheedi, M.T.; Mahdi, M.A. (Elsevier B.V., 2023)
Numerous saturable absorber (SA) fabrication methods have been proposed and employed in the development of ultrafast laser systems, particularly for microfiber-based SAs decorated with various 2D materials. However, the study on microfiber-SA with different transition lengths is still inadequate. This paper focuses on the design and fabrication method of black phosphorus/polydimethylsiloxane composite microfiber-based SA for ultrashort pulse generation. With optimized microfiber-SA dimensions of 30 mm (up/down taper), 1 mm (waist length) and 10 µm (waist diameter), black phosphorus/polydimethylsiloxane composite was spin-coated on the microfiber at 4000 rpm for 6 min. The integration of the microfiber-SA in an erbium-doped fiber laser exhibited pulse duration of 724 fs at center wavelength of 1560.18 nm. This work provides a guideline for the design of microfiber-based SA using spin-coating technique to maximize its laser performances.